Olfactory Impairment and Recovery in Zebrafish (Danio rerio) Following Cadmium Exposure - Chiara Maria Motta; Rosa Carotenuto; Chiara Fogliano; Luigi Rosati; Pabitra Denre; Raffaele Panzuto; Rossana Romano; Gianluca Miccoli; Palma Simoniello; Bice Avallone (Biology)
Anthropic activities have significantly elevated cadmium levels, making it a significant stressor in aquatic ecosystems. Present in high concentrations across water bodies, cadmium is known to bioaccumulate and biomagnify throughout the food chain. While the toxic effects of cadmium on the organs and tissues of aquatic species are well-documented, little is known about its impact on sensory systems crucial for survival. Consequently, this study investigated the impact of short-term exposure (96 h) to 25 µM cadmium chloride on the olfactory system of adult zebrafish. The research aimed to assess structural and functional changes in the zebrafish’s olfactory lamellae, providing a deeper understanding of how cadmium affects the sense of smell in this aquatic species. After exposure, cyto-anatomical alterations in the lamellae were analysed using light microscopy and immunocytochemistry. They revealed severe lamellar edema, epithelial thickening, and an increased number of apoptotic and crypt cells. Rodlet and goblet cells also increased by 3.5- and 2.5-fold, respectively, compared to control lamellae, and collagen density in the lamina propria increased 1.7-fold. Cadmium upregulated metallothioneins and increased the number of PCNA-positive cells. The olfactory function was assessed through a behavioural odour recognition test, followed by a recovery phase in which zebrafish exposed to cadmium were placed in clean water for six days. The exposed fish performed poorly, failing to reach food in five consecutive trials. However, lamellar damage was reduced after the recovery period, and their performance improved, becoming comparable to the control group. These results suggest that cadmium disrupts the sense of smell, and that recovery is possible after short-term exposure. This evidence sheds light on aspects of animal survival that are often overlooked when assessing environmental pollution.